SIMULATING THE EFFECT OF THERMAL ENVIRONMENT ON TOMATO WITH CROPGRO (DSSAT V4) MODEL - K.M, SUNIL; SARMA, SUNDARA; SINGH, K.S. BALRAJ (Annals of Agricultural Research, 2014)
The CROPGRO-Tomato (DSSAT V4) simulates tomato (Lycopersicn esculentum L.) growth, development and yield. The model requires calibration for tomato grown in the specific environmental conditions before going to assess the yield potential of tomato under Delhi conditions (semi-arid), The study was conducted to calibrate and test CROPGRO-Tomato for tomato growth, development and yield under different thermal environments. The model correctly predicted biomass, leaf are index (LA) and total yield. The model estimated the yield with in a mean error of 4.5 per cent. So the model should be a useful tool evaluating the potential yield of tomato under various thermal environments.